SARS-CoV 2 Infection (Covid-19) and Cardiovascular Disease in Africa: Health Care and Socio-Economic Implications - Okechukwu S. Ogah; Ejiroghene M. Umuerri; Adewole Adebiyi; Olanike A. Orimolade; Mahmoud U. Sani; Dike B. Ojji; Amam C. Mbakwem; Simon Stewart; Karen Sliwa (Ubiquity Press, 2021)
The current pandemic of SARS-COV 2 infection (Covid-19) is challenging health systems and communities worldwide. At the individual level, the main biological system involved in Covid-19 is the respiratory system. Respiratory complications range from mild flu-like illness symptoms to a fatal respiratory distress syndrome or a severe and fulminant pneumonia. Critically, the presence of a pre-existing cardiovascular disease or its risk factors, such as hypertension or type II diabetes mellitus, increases the chance of having severe complications (including death) if infected by the virus. In addition, the infection can worsen an existing cardiovascular disease or precipitate new ones. This paper presents a contemporary review of cardiovascular complications of Covid-19. It also specifically examines the impact of the disease on those already vulnerable and on the poorly resourced health systems of Africa as well as the potential broader consequences on the socio-economic health of this region.